Preparation method of low-dielectric moisture-proof organic silicon coating of quartz / quartz composite material
By applying a low dielectric moisture-proof coating with silicone resin as the main body on quartz composites, the problem of degradation of dielectric properties caused by water absorption in high temperature and humid environments is solved, and the high temperature stability and moisture-proof ability of the material are improved.
Patent Information
- Application Number
- CN202411734108.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
AI Technical Summary
When used in high temperature, vibration and humid environments, quartz composites are prone to adsorption of moisture, resulting in a decrease in dielectric performance, affecting the accuracy of the communication system.
A low-dielectric moisture-proof coating with silicone resin as the main body is used to prepare silicone impregnation liquid and coating, and a water-repellent protective film with low dielectric constant is formed by vacuum impregnation, room temperature surface drying and heating curing processes.
Effectively prevent quartz composite materials from absorbing water, improve their dielectric performance stability, enhance their tolerance to high temperature and humid environments, and ensure the accuracy and reliability of the communication system.
Abstract
Description
Technical Field
[0001] The invention discloses a quartz / quartz composite material surface organic silicon coating and a preparation method thereof, and relates to the field of quartz composite ceramic coatings, and in particular to a low-dielectric, high-temperature-resistant, moisture-proof quartz composite ceramic coating with organic silicon resin as a main body. Background Art
[0002] Usually, the communication window of an aircraft needs to face environmental tests such as high temperature, vibration, and humidity during operation. At present, the main materials selected are porous materials such as quartz fabric reinforced silica composite materials and porous silicon nitride. These materials have excellent high temperature resistance, ablation resistance, thermal shock resistance and other properties. At the same time, the radio wave transmission performance can meet the needs of high-precision radar. Among them, quartz composite materials have more openings and a large number of highly hydrophilic silanol groups on the pore surface. During storage and use, silanol groups are easy to adsorb water vapor in the atmosphere. The dielectric constant of water is relatively large, and the dielectric properties of quartz composite materials are greatly affected by the water content, resulting in reduced and unstable wave transmission of the communication window, which seriously affects the accuracy of the communication system.
[0003] The silicone resin system is a type of hydrophobic coating for quartz composite materials that has been widely studied. Considering the structure of the silicone resin itself, since its molecules contain a strong hydrophobic group -CH3, it has strong hydrophobicity, which can prevent water vapor in the air from being adsorbed and entering the interior of the material, and form a stable closed structure, thereby achieving the purpose of effective moisture-proofing and ensuring the stability and accuracy of the radar communication system. At the same time, silicone resin has good temperature resistance, strong bonding ability with quartz composite materials, and low dielectric loss, and is suitable for high-speed aircraft communication windows. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a low dielectric moisture-proof silicone coating of a quartz / quartz composite material, so as to overcome the defect that the dielectric properties of the existing quartz composite material are greatly affected by the water content, resulting in reduced and unstable wave transmittance of the communication window.
[0005] A method for preparing a low dielectric moisture-proof silicone coating of a quartz / quartz composite material, characterized in that it comprises the following steps:
[0006] Step 1, preparing an organic silicon impregnation liquid: the organic silicon impregnation liquid is prepared by mixing an organic silicon resin, a curing agent and a solvent at room temperature and pressure; the mass ratio of the organic silicon resin, the curing agent and the solvent is 1:0.001-0.01:1-2;
[0007] Step 2: placing the quartz / quartz composite material under vacuum conditions and impregnating it with an organic silicon impregnation liquid for 2 to 8 hours;
[0008] Step 3: Take out the quartz / quartz composite material from the silicone impregnation solution and dry it at room temperature; the surface drying time is 2 to 8 hours to achieve complete surface drying;
[0009] Step 4: Curing the quartz / quartz composite material which is dry after impregnation at a temperature of 60 to 100° C. for 1 to 5 hours;
[0010] Step 5: Grind the cured quartz / quartz composite material: remove the flash of the product, make the product reach the designed structural size and shape, and grind the surface to be smooth and flat;
[0011] Step 6: Prepare the organosilicon coating: the organosilicon coating is prepared by mixing an organosilicon resin and a diluent, wherein the mass ratio of the organosilicon resin to the diluent is 1:1-2;
[0012] Step 7: spray the prepared organic silicon coating evenly onto the surface of the quartz / quartz composite material, and heat and cure it after the surface is dry. After the curing is completed, a low dielectric moisture-proof organic silicon coating is obtained.
[0013] Wherein, the curing agent described in step 1 is amine, acid or peroxide; the solvent is one or a mixture of isopropanol, acetic acid, ether, ketone and benzene.
[0014] The surface drying time described in step 7 is 2 to 8 hours; the curing temperature after surface drying is 60 to 80° C., and the curing time is 1 to 5 hours.
[0015] The curing agent described in step 1 is amine and the solvent is isopropanol.
[0016] The invention is beneficial in that:
[0017] 1) The present invention adopts silicone resin as the main body to prepare the impregnation liquid, vacuum impregnates the quartz composite ceramic material in the impregnating agent, dries the surface at room temperature, and is dried and cured at 60-100°C. After cooling to room temperature, the flash is repaired, and the prepared high-temperature resistant and hydrophobic silicone coating is sprayed. After the surface is dried, it is cured at 60-100°C to obtain a quartz composite ceramic moisture-proof coating with silicone resin as the main body, which has the advantages of high and low temperature resistance, low dielectric constant, hydrophobicity, weather resistance, etc., and has a simple process.
[0018] 2) Using the advantages of high and low temperature resistance, low dielectric constant, hydrophobicity, and weather resistance of silicone resin as a moisture-proof coating, the moisture-proof ability of quartz composite materials can be improved while maintaining good dielectric properties and high temperature stability. The coating is prepared by combining dipping and spraying, which enables the silicone resin to be evenly and completely attached to the surface of the quartz composite ceramic material and block the microscopic pores inside the ceramic, thereby improving the density of the ceramic material. DETAILED DESCRIPTION
[0019] In order to solve the above technical problems, the present invention provides a method for preparing a quartz composite ceramic moisture-proof coating with an organic silicon resin as the main body, which is characterized in that it comprises the following steps:
[0020] 1. Prepare an organic silicon impregnation liquid, which consists of three parts: an organic silicon resin, a curing agent and a solvent. The organic silicon resin is a combination of one or more of HLM888, SAR-2, SAR-9 and MR-30, preferably SAR-2; the curing agent is an amine, an acid and a peroxide, preferably an amine curing agent; the solvent is isopropanol, acetic acid, ether, ketone, benzene and a combination thereof, preferably isopropanol; the mass ratio of the three is 1: (0.001-0.01): (1-2), preferably 1: (0.002-0.005): 1.2.
[0021] 2. Place the quartz composite material in the impregnation liquid for vacuum impregnation and take it out after 8 hours of impregnation.
[0022] 3. Allow the quartz composite material to dry at room temperature for 2-8 hours.
[0023] 4. Curing by heating, the curing temperature is 60-80°C, preferably 80°C; the curing time is 1-5h.
[0024] 5. After cooling, repair the flash to make the product reach the designed size and shape, and polish the surface to be smooth and flat.
[0025] 6. Prepare an organosilicon coating, which consists of an organosilicon resin and a diluent, wherein the organosilicon resin is a combination of one or more of HLM888, SAR-2, SAR-9 and MR-30, preferably SAR-2; the diluent is isopropyl alcohol, acetic acid, ether, ketone, benzene and a combination thereof, preferably isopropyl alcohol; the mass ratio of the two is 1: (1-2), preferably 1: 1.5.
[0026] 7. Spray the silicone coating evenly onto the surface of the quartz composite material
[0027] 8. Surface drying at room temperature, the surface drying time is 2-8 hours.
[0028] 9. Curing by heating, the curing temperature is 60-80°C, preferably 80°C; the curing time is 1-5h.
[0029] The present invention is further described in detail below in conjunction with specific embodiments:
[0030] Example
[0031] A high-temperature wave-transmitting hydrophobic moisture-proof coating for quartz composite ceramics and a preparation method thereof, wherein the preparation process comprises the following steps:
[0032] 1. Prepare the silicone impregnation solution: weigh 100 g of SAR-2 silicone resin, 0.3 g of ethylenediamine, and 120 g of isopropanol, mix well and stir for 1 hour.
[0033] 2. Place the quartz composite material in the impregnation liquid for vacuum impregnation and take it out after 8 hours of impregnation.
[0034] 3. Allow the quartz composite material to dry at room temperature for 4 hours.
[0035] 4. Heat up and cure, the curing temperature is 80℃ and the curing time is 1h.
[0036] 5. After cooling, repair the flash to make the product reach the designed size and shape, and polish the surface to be smooth and flat.
[0037] 6. Prepare the organosilicon coating: weigh 100 g of SAR-2 organosilicon resin and 150 g of isopropanol, mix well and stir for 1 hour.
[0038] 7. Place the composite material on a rotating platform and rotate it at a preset speed to evenly spray the silicone coating onto the surface of the quartz composite material.
[0039] 8. Surface drying at room temperature, surface drying time is 4 hours.
[0040] 9. Heat up and cure, the curing temperature is 80℃ and the curing time is 1h.
[0041] 10. When cooled to room temperature, the silicone resin adheres to the inside and surface of the quartz composite material.
[0042] The preparation method provided by the above technical solution utilizes the characteristics of silicone resin itself, which has high temperature resistance, moisture resistance and water resistance, and low dielectric constant and dielectric loss. It is impregnated and coated on the surface of the quartz composite material to form a continuous low dielectric, high barrier, and high temperature resistant protective film, thereby solving the problem of severe loss of electrical performance caused by moisture absorption of quartz composite ceramic-based antenna cover in actual application environment.
[0043] In step 1 of the above technical solution, the impregnation liquid can effectively improve the coating efficiency and coating integrity of the silicone resin, and help the silicone resin form a continuous and uniformly thick coating on the surface of the composite material. In step 1 of the above technical solution, since SAR-2 resin is selected, isopropanol with good solubility is selected as the solvent, and it is completely dissolved by sufficient stirring. If other types or brands of resins are selected, the solvent should be selected specifically, but the boiling point of the solvent should not be too high to facilitate the subsequent solvent removal, and the amount of the solvent should not be too much or too little to avoid affecting the subsequent process.
[0044] In step 1 of the above technical solution, since SAR-2 resin is selected, ethylenediamine, a curing agent suitable for the resin, is selected specifically and fully dissolved by stirring. If other types or brands of resins are selected, the curing agent should be selected specifically, and the amount of the curing agent should not be too much or too little, so as to avoid over-fast curing or insufficient curing.
[0045] In step 2 of the above technical solution, the quartz composite material is a quartz composite material prepared by the silica sol method, and the silicone resin coated by this solution improves its waterproof and moisture-proof ability. The quartz composite material should complete the previous multiple "impregnation-curing-pyrolysis" processes to form a dense composite material, and after precision machining, the dimensional accuracy meets the product requirements. This technical solution only prepares the surface coating and does not operate the internal main body.
[0046] In step 3 of the above technical solution, the surface drying time can be adjusted according to the type of solvent, ventilation environment, and surface drying temperature.
[0047] In step 4 of the above technical solution, the curing time and temperature can be adjusted according to the type and amount of the curing agent and the type of resin.
[0048] In step 5 of the above technical solution, the operation is only to repair the flash, which does not affect the product size. The product size has been determined before all operations of the solution.
[0049] In step 6 of the above technical solution, a curing agent may be appropriately added according to the proportion in step 1.
[0050] In step 7 of the above technical solution, the preset rotation speed of the rotating platform is 20 rpm. Too fast or too slow rotation speed will cause local defects on the surface or too thick spraying.
[0051] In step 8 of the above technical solution, the surface drying time can be adjusted according to the type of solvent, ventilation environment, and surface drying temperature.
[0052] In step 9 of the above technical solution, the curing time and temperature can be adjusted according to the type and amount of the curing agent and the type of resin.
[0053] The invention discloses a high-temperature wave-transmitting hydrophobic moisture-proof coating for quartz composite ceramics and a preparation method thereof, which is characterized in that an organic silicon impregnation liquid for sealing is prepared; a high-temperature hydrophobic organic silicon coating is prepared; the quartz composite ceramic material is vacuum impregnated in the organic silicon impregnation liquid, dried and solidified at 60-100°C after being surface-dried at room temperature, sprayed with the high-temperature hydrophobic organic silicon coating after cooling and repairing the flash edge, and dried and solidified again at 60-100°C after being surface-dried at room temperature to obtain the high-temperature wave-transmitting hydrophobic moisture-proof coating of the quartz composite ceramics. The quartz composite ceramic coating prepared by the invention is mainly composed of organic silicon resin, has the advantages of high and low temperature resistance, low dielectric constant, hydrophobicity, weather resistance, etc., and has a simple process, and can meet the performance requirements of products working in extreme environments such as aerospace communication windows.
[0054] A method for preparing a low dielectric moisture-proof silicone resin coating for a quartz composite material, characterized in that it comprises the following steps:
[0055] Prepare an organic silicon impregnation liquid, place the quartz composite material in the impregnation liquid for vacuum impregnation, dry it at room temperature and heat it up to cure it. After cooling, repair the flash, prepare an organic silicon coating, spray the organic silicon coating evenly on the surface of the quartz composite material, dry it at room temperature and heat it up to cure it.
[0056] The organic silicon impregnation liquid consists of three parts: organic silicon resin, curing agent and solvent, wherein the organic silicon resin brand is a combination of one or more of HLM888, SAR-2, SAR-9 and MR-30, preferably SAR-2; the curing agent is amines, acids and peroxides, preferably amine curing agents; the solvent is isopropanol, acetic acid, ether, ketone, benzene and a combination thereof, preferably isopropanol; the mass ratio of the three is 1: (0.001-0.01): (1-2), preferably 1: (0.002-0.005): 1.2.
[0057] The surface drying time after the immersion is 2-8 hours.
[0058] The curing temperature after the impregnation and surface drying is 60-80° C., preferably 80° C.; the curing time is 1-5 hours.
[0059] After curing, it needs to be polished to remove the flash of the product, make the product reach the designed size and shape, and polish the surface to be smooth and flat.
[0060] The organic silicone coating consists of two parts: an organic silicone resin and a diluent, wherein the organic silicone resin is a combination of one or more of SAR-2, SAR-9 and MR-30, preferably SAR-2; the diluent is isopropyl alcohol, acetic acid, ether, ketone, benzene and a combination thereof, preferably isopropyl alcohol; the mass ratio of the two is 1:(1-2), preferably 1:1.5.
[0061] The surface drying time after spraying the organic silicon coating is 2-8 hours.
[0062] The curing temperature after the organic silicon coating is sprayed and surface dried is 60-80° C., preferably 80° C.; the curing time is 1-5 hours.
Claims
1. A method for preparing a low dielectric moisture-proof silicone coating of a quartz / quartz composite material, characterized in that: It includes the following steps: Step 1, preparing an organic silicon impregnation liquid: the organic silicon impregnation liquid is prepared by mixing an organic silicon resin, a curing agent and a solvent at room temperature and pressure; the mass ratio of the organic silicon resin, the curing agent and the solvent is 1:0.001-0.01:1-2; Step 2: placing the quartz / quartz composite material under vacuum conditions and impregnating it with an organic silicon impregnation liquid for 2 to 8 hours; Step 3: Take out the quartz / quartz composite material from the silicone impregnation solution and dry it at room temperature; the surface drying time is 2 to 8 hours to achieve complete surface drying; Step 4: Curing the quartz / quartz composite material which is dry after impregnation at a temperature of 60 to 100° C. for 1 to 5 hours; Step 5: Grind the cured quartz / quartz composite material: remove the flash of the product, make the product reach the designed structural size and shape, and grind the surface to be smooth and flat; Step 6: Prepare the organosilicon coating: the organosilicon coating is prepared by mixing an organosilicon resin and a diluent, wherein the mass ratio of the organosilicon resin to the diluent is 1:1-2; Step 7: spray the prepared organic silicon coating evenly onto the surface of the quartz / quartz composite material, and heat and cure it after the surface is dry. After the curing is completed, a low dielectric moisture-proof organic silicon coating is obtained.
2. The method for preparing a low dielectric moisture-proof silicone coating of a quartz / quartz composite material according to claim 1, characterized in that: The curing agent described in step 1 is amine, acid or peroxide; the solvent is one or a mixture of isopropyl alcohol, acetic acid, ether, ketone and benzene.
3. The method for preparing a low dielectric moisture-proof silicone coating of a quartz / quartz composite material according to claim 1, characterized in that: The surface drying time described in step seven is 2 to 8 hours; the curing temperature after surface drying is 60 to 80° C., and the curing time is 1 to 5 hours.
4. The method for preparing a low dielectric moisture-proof silicone resin coating of a quartz composite material according to claim 2, characterized in that: The curing agent described in step 1 is amine and the solvent is isopropanol.
Citation Information
Patent Citations
Dampproof fiber-reinforced silica ceramic composite material and method
CN108285354A
SiO2f / SiO2 ceramic damp-proof sealing coating and preparation method thereof
CN111718206A
Hydrophobic silicon dioxide ceramic composite material and preparation method thereof
CN116730743A